Upaya Meningkatkan Pemahaman Pelajaran PAI Dengan Menggunakan Metode Pembelajaran Simulasi Di Sekolah SMP Muhammadiyah 50 Medan - Munawir Pasaribu; Risawan Sinamo (Cattleya Darmaya Fortuna, 2022)
Based on field experience the understanding of the material received by students in pie lessons is still not optimal, this study uses the Pie simulation learning method. Muhammadiyah 50 Medan .Development of PKP Professional Capability which is carried out in one month. The location of the research subjects is class VII, VIII, IX. Islamic religious education in general can be understood as an effort to increase students' faith, understanding, appreciation and practice of the Islamic religion so that they become Muslim individuals who believe and are pious and have noble character in personal, community, nation and state life. This study is to determine the evaluation of the simulation process Islamic religious education learning at Muhammadiyah 50 Medan Middle School is in accordance with the planned program. a) By using the method the teacher has used media/approaches in the variation learning process